Produção de biodiesel a partir de misturas de óleos e óleos interesterificados: estudo cinético da reação de transesterificação - Melo, Lucas Natã de (2019)
Biodiesel is a fuel produced from renewable sources, many of them found in Brazilizan territory, through different processes, among which transsesterification is the most used one. Gás chromatography is the most used technique for the identification and quantification of formed biodiesel, as it is a very selective and efficient technique. The determination of these compounds is used to evaluate the quality of the produced biodiesel and to obtain important information about the feedstock selection, the biodiesel performance as a fuel and, especially, the selection of the catalyst to be used. In this work it is intended to study the reaction kinetcs of the transesterification of a mixture of oils (soybean:castor) ando of the same mixture after interesterification, that is, the mixture underwent a randomization processo f the arrangement of the fatty acids esterified to triacylglycerols (TAGs) molecules. Hence it Will be possible to verify IF the presence and /or location of fatty acids in TAG molecules determine the reaction yield. In this regard, analytical methodologies based on gás chromatography (GC-FID) and high performance liquid chromatography (HPLC-UV) were applied to identify the formation of the interesterified oils and evaluatethe yield of fatty acid methyl esters (FAME) production from a simple blendof these oils and from interesterified oils. Infrared spectroscopoc analysis showed that there is no isomerization of the cis insaturations of fatty acids after interesterification. The on-column injection methodology was the most suitable to verify the formation of momo- and diacylglycerols after interesterification, since the split-mode injection methodology was associated with the termal degradation of TAGs. Increasing the amounts of castor oil in the blends provided a decrease in the efficiency of interesterification using 0,4% of catalyst, as only the soybean:castoroil 2:1 blend showed substantial was successful for this mixture. However, low FAME yield was obtained after transesterification of this interesterified blemd when compared to its simple mixture, indicating that the location of the fatty acid moieties in TAG molecules prevails over the fatty acid composition of the reaction mixture and is determining for the transesterification kinetcs.